2015
DOI: 10.1007/s10653-015-9774-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of Cd and Pb in tailings from a zinc smelting in Brazil: implications for human health

Abstract: Soils and wastes enriched with heavy metals may present ecological and human health risks. A considerable number of mining areas exist in Brazil, where high levels of metals have been found. However, studies of bioaccessibility of metals in soils/tailings from these areas are scarce, despite their potential informational contribution concerning exposure risks of residents near these areas. This study evaluated tailings collected from four sites of a zinc smelting area located in Brazil with aims to: (1) evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Since the onset of industrial revolution, mining and smelting activities have been at forefront of economic development of many countries. Mining activities generate employment, while also producing a wide variety of minerals that can have countless uses in various contexts (Ono et al, ;Dino et al, 2018a). Yet, mining and dressing activities have resulted in the generation of large quantities of waste and degraded soils.…”
Section: Introductionmentioning
confidence: 99%
“…Since the onset of industrial revolution, mining and smelting activities have been at forefront of economic development of many countries. Mining activities generate employment, while also producing a wide variety of minerals that can have countless uses in various contexts (Ono et al, ;Dino et al, 2018a). Yet, mining and dressing activities have resulted in the generation of large quantities of waste and degraded soils.…”
Section: Introductionmentioning
confidence: 99%
“…The key words used were "bioaccessibility", "Brazil", "soil" and "sediments". Of these 13 papers, one was carried out with soils from state of São Paulo , Souza et al, 2018, one with soils from Amazon forest (Moreira et al, 2018), one with soils of the city of Três Marias, Minas Gerais state (MG) (Ono et al, 2016), two articles and three procedures with soils of Paracatu, MG (Ono et al, 2012a, b;Guilherme et al, 2014;Ng et al, 2014a, b, Ciminelli et al, 2018, two articles with soils from Adrianópolis, State of Paraná (Bosso & Enzweiler, 2008a;Bosso et al, 2008) and a review (Bosso & Enzweiler, 2008b). While around 350 articles and 13 international reviews were found at the Scopus research base, most of them were published by Chinese, American and British researchers.…”
Section: Introductionmentioning
confidence: 99%